2015
DOI: 10.3857/roj.2015.33.3.198
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of curative radiotherapy in patients with vulvar cancer: results of the retrospective KROG 1203 study

Abstract: PurposeWe evaluated the prognostic factors and clinical outcomes of 56 patients with vulvar cancer treated with curative radiotherapy (RT) or concurrent chemoradiotherapy.Materials and MethodsOverall survival (OS) and disease-free survival (DFS) were assessed retrospectively. Prognostic factors evaluated included age, International Federation of Gynecology and Obstetrics (FIGO) stage, TNM classification, tumor size, treatment modality, RT duration, and RT field. The association between the tumor human papillom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…31,41,42,44,46 Additionally, two studies were from Brazil 33,39 and one study was conducted in Korea. 40 The age of the included women were similar in all studies, with reported age means or medians ranging from early 60s to early 70s. Fifteen studies 30,[32][33][34][35][36][37][38][39][41][42][43][44][45][46] included only women with vulvar SCCs.…”
Section: Cancer Epidemiologymentioning
confidence: 75%
See 4 more Smart Citations
“…31,41,42,44,46 Additionally, two studies were from Brazil 33,39 and one study was conducted in Korea. 40 The age of the included women were similar in all studies, with reported age means or medians ranging from early 60s to early 70s. Fifteen studies 30,[32][33][34][35][36][37][38][39][41][42][43][44][45][46] included only women with vulvar SCCs.…”
Section: Cancer Epidemiologymentioning
confidence: 75%
“…The majority of studies originated from Europe ( n = 10) and USA or Canada ( n = 5) . Additionally, two studies were from Brazil and one study was conducted in Korea . The age of the included women were similar in all studies, with reported age means or medians ranging from early 60s to early 70s.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations